Injury patterns of rear seat occupants in frontal impact: an in-depth crash investigation study. Issue 3 (9th December 2015) - Beck, Ben; Bilston, Lynne E; Brown, Julie
Abstract : Objective: Rear seat occupants are now at a higher risk of injury relative to front seat occupants and there is a need for enhanced protection. This study aimed to examine the pattern of injury, injury mechanisms and injury sources to restrained motor vehicle rear seat occupants involved in a frontal impact. Methods: Cases involving restrained rear seat occupants aged 9 years and older involved in frontal crashes were prospectively collected from in-depth crash investigations collected in New South Wales and Victoria, Australia, between 2000 and 2010. Structured occupant and driver interviews were conducted to ascertain crash parameters, medical records were reviewed and detailed injury descriptions were recorded using the abbreviated injury scale (AIS). Vehicle and scene inspections were also conducted and injury sources determined. Results: The dataset included 29 rear seat occupants aged 9–80 years. AIS2+ injuries were most commonly observed in the chest and abdomen. Chest injuries were more commonly observed in older occupants, while abdominal and thoracolumbar spine injuries were mostly observed in younger occupants. The seat belt was the most common source of injury to rear seat occupants. Conclusions: The seat belt is the most common source of injury to rear seat passengers in frontal impact with variations in injury with age. There is a need to provide appropriate belt fit and better control seat belt loads for rear seat passengers. This could be achieved, at least in part, with existing technologies currently used in front seat positions, although novel technologies may also be useful.